GENERAL LAWS OF GROWTH AND DEVELOPMENT OF THE ORGANISM OF CHILDREN AND ADOLESCENTS (Proceedings of International Educators Conference, 2023)
Properly raise children, it is necessary to know the main characteristics of their body, such as growth and development. Growth and development is a characteristic of the human body, like all living organisms. All-round growth and development of the organism begins from the moment of its appearance. These two processes are considered complex, integrated and interconnected .